Pathways to meaning: how family functioning shapes meaning in life through school belonging among Chinese adolescents - Xiaoxia Deng; Jie Cao; Jinhua Li; Beni Widarman Yus Kelana (Frontiers in Psychology, 2026)
Introduction The relationship between family functioning, school belonging, and meaning in life has been rarely investigated in China, especially among early adolescents. Drawing on the Overlapping Spheres of Influence (OSI) theory, this study aims to explore the impact of family functioning on adolescents’ meaning in life and to examine the mediating role of school belonging in this relationship. Methods A multi-stage stratified sampling method was employed to recruit 410 valid participants from middle schools in China. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both the measurement and structural models, including mediation analysis via bootstrapping with 5,000 resamples. Results The results indicated that both family functioning and school belonging positively predict meaning in life among adolescents. Furthermore, school belonging can mediate the relationship between family functioning and meaning in life, accounting for 55.6% of the total effect. The model explained 33.0% of the variance in meaning in life, with adequate predictive relevance. Conclusions These findings confirm that family functioning influences adolescents’ meaning in life both directly and indirectly through school belonging, with the indirect pathway being stronger. This highlights that a supportive family environment fosters psychological readiness for adolescents to connect with school, where their meaning in life is largely constructed. The study also offers practical implications for educators, mental health professionals, and policymakers to promote family-school partnerships and strengths-based interventions that enhance adolescent well-being.